Prevalence and determinants of risky sexual practice in Ethiopia: Systematic review and Meta-analysis - Achenef Asmamaw Muche; Getachew Mullu Kassa; Abadi Kidanemariam Berhe; Gedefaw Abeje Fekadu (BMC, 2017)
Abstract Background Risky sexual practice is a major public health problem in Ethiopia. There are various studies on the prevalence and determinants of risky sexual practice in different regions of the country but there is no study which shows the national estimate of risky sexual practices in Ethiopia. Therefore, this review was conducted to estimate the national pooled prevalence of risky sexual practice and its risk factors in Ethiopia. Methods The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guideline was followed to review published and unpublished studies in Ethiopia. The databases used were; PubMed, Google Scholar, CINAHL and African Journals Online. Search terms were; risky sexual behavior, risky sexual practice, unprotected sex, multiple sexual partner, early sexual initiation, and/or Ethiopia. Joanna Briggs Institute Meta-Analysis of Statistics Assessment and Review Instrument was used for critical appraisal. The meta-analysis was conducted using Review Manager software. Descriptive information of studies was presented in narrative form and quantitative results were presented in forest plots. The Cochran Q test and I 2 test statistics were used to test heterogeneity across studies. The pooled estimate prevalence and the odd ratios with 95% confidence intervals were computed by a random effect model. Results A total of 31 studies with 43,695 participants were included in the meta-analysis. The pooled prevalence of risky sexual practice was 42.80% (95% CI: 35.64%, 49.96%). Being male (OR: 1.69; 95% CI: 1.21, 2.37), substance use (OR: 3.42; 95% CI: 1.41, 8.31), peer pressure (OR: 3.41; 95% CI: 1.69, 6.87) and watching pornography (OR: 3.6; 95% CI: 2.21, 5.86) were factors associated with an increase in risky sexual practices. Conclusions The prevalence of risky sexual practices is high in Ethiopia. Being male, substance use, peer pressure and viewing pornographic materials were found to be associated with risky sexual practices. Therefore, life skills training is recommended to reduce peer pressure among individuals. Interventions should be designed to reduce substance use and viewing pornography.